Characterization of residual stresses in fiber metal laminate interfaces – A combined approach applying hole-drilling method and energy-dispersive X-ray diffraction. (1st November 2022) - Wu, T.; Degener, S.; Tinkloh, S.; Liehr, A.; Zinn, W.; Nobre, J.P.; Tröster, T.; Niendorf, T.
Abstract: Fiber metal laminates (FMLs) can be manufactured by direct bonding of fiber reinforced plastics (FRP) and metals using advanced manufacturing approaches, e.g., the prepreg-press-technology. Such materials gain high interest in lightweight applications as they benefit from the superior characteristics of both materials. However, residual stresses are induced in the manufacturing process mainly due to the difference in thermal expansion coefficients between FRP and metal. These residual stresses can lead to the delamination at the transition zone/ interface between FRP and metal and, thus, detrimentally affect the structural integrity and the durability of the FML structure. The objective of the present work is to introduce reliable experimental approaches to accurately measure the distribution of residual stresses across the thickness of the FML, with a special focus on the interface between metal and FRP. Symmetric FMLs with a specific stacking sequence of FRP/steel/FRP are designed and fabricated for residual stress analysis using different approaches, i.e., relaxation and diffraction methods, as well as for results comparison and validation purposes. The incremental hole drilling method (IHD) is used to determine the residual stresses across the thickness of the FMLs. By choosing FRPs with a relatively small thickness, a reliable measurement using IHD can even be achieved across the transition zone between FRP and metal. The energy-dispersive X-ray diffraction method (ED-XRD), as an advanced non-destructive approach, is employed for in-depth residual stress measurement in the metallic part of the FMLs. Each measurement method is characterized by its own advantages, intrinsic limitations as well as uncertainty sources. The obtained results give confidence that both methods are able to assess the qualitative distribution as well as the absolute magnitudes of residual stresses in the FMLs. Based on the approach detailed the reliability of the two measurement methods is cross-validated.